Requirements Gathering for the Development of a Game for Therapy Sessions with Autistic Children to Encourage Social Communication - Peixoto, Henrique de Oliveira; Moraes, Guilherme Brun; Nunes, Eunice P. dos Santos; Borges, Luciana Correia L. F.; Rodrigues, Kamila Rios da Hora (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2022: Proceedings of the 2nd Life Improvement in Quality by Ubiquitous Experiences WorkshopDO - 10.5753/lique.2022.19996, 2022)
Children with Autism Spectrum Disorder (ASD) are very sensitive to social situations and have difficulties interacting with their peers. In order to mitigate this difficulty, therapeutic treatment is often used. Games, which can be used for many different purposes, can also be used as an Assistive Technology (AT) in the therapy process, in order to encourage social communication and collaboration, which are very important skills in daily life. A Systematic Review (SR) was conducted using two research questions to gather more information about the theme. In parallel, a survey was applied to support the results of the SR. We found that genres of games that are likely to enhance collaboration are collaborative brain games (such as puzzle or memory games). We also found that games should be very minimalist (with a low number of players) and contain clear language, avoiding figures of speech. The results of this paper will be used as a basis to develop a game as an AT for the therapy of children with ASD in the future.